2014
DOI: 10.5194/npg-21-405-2014
|View full text |Cite
|
Sign up to set email alerts
|

Alfvén waves in space and astrophysical dusty plasmas

Abstract: Abstract. In this paper, we present some results of previous works on Alfvén waves in a dusty plasma in different astrophysical and space regions by taking into account the effect of superthermal particles on the dispersive characteristics. We show that the presence of dust and superthermal particles sensibly modify the dispersion of Alfvén waves. The competition between different damping processes of kinetic Alfvén waves and Alfvén cyclotron waves is analyzed. The nonlinear evolution of Alfvén waves to chaos … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 105 publications
0
8
0
Order By: Relevance
“…( 15)-( 17) are good approximations for the resonance frequencies in three-component plasmas. 15), (16), and (17) We note that this study neglects the effects of the thermal pressure on the plasma waves. Compared with the usual fast, Alfvén, and slow modes in electron and proton plasmas [24] , the magnetosonic waves carried by the heavy charged particles are driven by the thermal pressure of the heavy charged particles and magnetic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…( 15)-( 17) are good approximations for the resonance frequencies in three-component plasmas. 15), (16), and (17) We note that this study neglects the effects of the thermal pressure on the plasma waves. Compared with the usual fast, Alfvén, and slow modes in electron and proton plasmas [24] , the magnetosonic waves carried by the heavy charged particles are driven by the thermal pressure of the heavy charged particles and magnetic pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of charged dust particles also modifies the scenario of the Alfven waves [23][24][25][26][27][28] by enhancing their frequency, modifying the dispersion relation, and showing a damping effect due to dust charge fluctuation dynamics. Jatenco-Pereira et al [29] showed the sensible modification of the dispersion relation of Alfvén waves in the presence of dust and superthermal particles. They analysed the competition between different damping processes of kinetic Alfven waves and Alfven cyclotron waves and their applications in the auroral regions of space plasmas, stellar winds, and astrophysical plasmas.…”
Section: Introductionmentioning
confidence: 99%
“…Several observations by various satellite missions have reported the presence of velocity distributions that exhibit non‐Maxwellian features [ 38,39 ] and can be modelled by generalized Lorentzian profiles, in which high‐energy tails due to the presence of energetic particles appear. [ 40–42 ] Such superthermal plasmas are found in the magnetospheres of various planets, e.g. Earth, Mercury, and Saturn.…”
Section: Introductionmentioning
confidence: 99%